Squamous cell carcinoma of the renal parenchyma presenting as hydronephrosis: a case report and review of the recent literature - Zhang, Xirong (BMC Urol, 2020)
BACKGROUND: Primary squamous cell carcinoma of the renal parenchyma is extremely rare, only 5 cases were reported. CASE PRESENTATION: We probably report the fifth case of primary Squamous cell carcinoma (SCC) of the renal parenchyma in a 61-year-old female presenting with intermittent distending pain for 2 months. Contrast-enhanced computed tomography (CECT) revealed hydronephrosis of the right kidney, but a tumor cannot be excluded completely. Finally, nephrectomy was performed, and histological analysis determined that the diagnosis was kidney parenchyma squamous cell carcinoma involving perinephric adipose tissue. CONCLUSIONS: The present case emphasizes that it is difficult to make an accurate preoperative diagnosis with the presentation of hidden malignancy, such as hydronephrosis.